Production of extracellular L- asparaginase by halophilic bacterium vibrio sp. - Mahdis Zolfaghar; Mohammad Ali Amoozegar; Khosro Khajeh (Biological Journal of Microorganism, 2016)
Introduction: L-Asparaginase is an anti-neoplastic drug used in lymphoblastic leukemia chemotherapy. Nowadays, this enzyme derived from bacterial sources, mostly L-asparaginase II from Escherichia coli and in lesser amount L-asparaginase of Erwinia sp. has medical utilization. The long-term usage of these agents leads to allergic reactions; therefore new L- asparaginase with new immunological characteristics is required. Halophilic bacteria might contain L-asparaginase with novel immunological properties that can be used in hypersensitive patients.